The chemoprotective effect of anti-platelet agents on cancer incidence in people with non-alcoholic fatty liver disease (NAFLD): a retrospective cohort study - Matthew Anson; Jun Shang Poon; Alex E. Henney; David Riley; Gema H. Ibarbaru; Cyril Sieberhagen; Daniel J. Cuthbertson; Uazman Alam; Theresa Hydes (BMC Medicine, 2024)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is associated with an increased incidence of hepatic and extrahepatic cancers, in particular those linked to obesity. In people with chronic liver disease, aspirin may confer protection against hepatocellular carcinoma (HCC). We explore the potential chemoprotective effect of aspirin/other anti-platelet agents on obesity-related cancers, including HCC in people with NAFLD. Methods We performed a retrospective cohort study of anonymised electronic medical records using the TriNetX network (Cambridge, MA, USA), a global federated database. We identified adults aged 18 or over with a diagnosis of NAFLD, prior to commencing antiplatelet agents. Two groups were created: antiplatelet (1) versus no antiplatelet use (2). We propensity score matched for nine variables. Antiplatelet use was defined as aspirin, ticagrelor, cangrelor, clopidogrel or prasugrel use for at least 1 year. The outcomes of interest were incidence of HCC and other obesity-related cancers. Follow-up was for 5 years. We performed subgroup analyses on aspirin users only and stratified findings for sex and age. Sensitivity analysis was conducted on individuals with 3- and 5-year aspirin exposure. Results Post matching, there were 42,192 people per group. Antiplatelet use in people with NAFLD was associated with statistically significant reduction in all obesity-related cancers (HR 0.71, 95% CI 0.65–0.78, p < 0.001) and individually for HCC (HR 0.52, 95% CI 0.40–0.68, p < 0.001), breast carcinoma (HR 0.78, 95% CI 0.66–0.92, p = 0.003), pancreatic carcinoma (HR 0.61, 95% CI 0.47–0.78, p < 0.001) and colorectal carcinoma (HR 0.68, 95% CI 0.56–0.84, p < 0.001). For women, there was a significant reduction in risk of ovarian carcinoma (HR 0.75, 95% CI 0.57–0.98, p = 0.034). Aspirin monotherapy was similarly associated with reduced incidence of HCC (HR 0.46, 95% CI 0.32–0.64, p < 0.001) and all obesity-related cancers (HR 0.71, 95% CI, 0.56–0.90, p = 0.004), with benefits observed in males (HR 0.71, 95% CI 0.56–0.90, p = 0.004), females (HR 0.77, 95% CI 0.67–0.88, p < 0.001) and in older (HR 0.72, 95% CI 0.63–0.82, p < 0.001) but not younger people (HR 0.78, 95% CI 0.60–1.03, p = 0.589). Conclusions Aspirin/antiplatelet agents may have a role in primary cancer prevention in people living with NAFLD.